2020
DOI: 10.3389/fcimb.2020.590657
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Differences of Type 1 Restriction-Modification Allele Variants in Experimental Listeria monocytogenes Meningitis

Abstract: Background: L. monocytogenes meningoencephalitis has a mortality rate of up to 50% and neurofunctional sequelae are common. Type I restriction-modification systems (RMS) are capable of adding methyl groups to the host genome. Some contain multiple sequence recognition (hsdS) genes that recombine, resulting in distinct DNA methylation patterns and patterns of gene expression. These phenotypic switches have been linked to virulence and have recently been discovered in multiple clonal complexes of L. monocytogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Such shifts between phenotypic forms are also observed in other bacteria such as Streptococcus pneumoniae ( Manso et al, 2014 ). A previous study using a neonatal rat-based Listeria meningitis model and an L. monocytogenes CC4 strain carrying a similar type I RMS as N12-0794 showed that phase variations linked to these systems result in altered disease severity outcomes ( Zbinden et al, 2020 ). These phase variable epigenetic modifications might allow some strains to finely tune their virulence gene expression, only expressing them when specific host conditions are encountered.…”
Section: Discussionmentioning
confidence: 99%
“…Such shifts between phenotypic forms are also observed in other bacteria such as Streptococcus pneumoniae ( Manso et al, 2014 ). A previous study using a neonatal rat-based Listeria meningitis model and an L. monocytogenes CC4 strain carrying a similar type I RMS as N12-0794 showed that phase variations linked to these systems result in altered disease severity outcomes ( Zbinden et al, 2020 ). These phase variable epigenetic modifications might allow some strains to finely tune their virulence gene expression, only expressing them when specific host conditions are encountered.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the expression of hsdSC and D worsened the disease onset in L. monocytogenes meningitis (Zbinden et al, 2020). This observation shows important phenotypical switching that has crucial role in regulating the virulence of CNS infections by L. monocytogenes (Zbinden et al, 2020). Nevertheless, further studies are necessary to investigate how this therapy can also be effective in reducing brain injury.…”
Section: Bacterial Meningitismentioning
confidence: 98%
“…L. monocytogenes meningoencephalitis has a mortality rate of up to 50%, and severe neurofunctional sequelae are prevalent. Zbinden et al have identified that L. monocytogenes expressing multiple sequence recognition (hsdS) A causes less damage than when other hsdS genes (B, C or D) are present (Zbinden et al, 2020). On the other hand, the expression of hsdSC and D worsened the disease onset in L. monocytogenes meningitis (Zbinden et al, 2020).…”
Section: Bacterial Meningitismentioning
confidence: 99%
See 1 more Smart Citation
“…Such shifts between phenotypic forms are also observed in other bacteria such as Streptococcus pneumoniae (Manso et al, 2014). A previous study using a neonatal ratbased Listeria meningitis model and an L. monocytogenes CC4 strain carrying a similar type I RMS as N12-0794 showed that phase variations linked to these systems result in altered disease severity outcomes (Zbinden et al, 2020). These phase variable epigenetic modifications might allow some strains to finely tune their virulence gene expression, only expressing them when specific host conditions are encountered.…”
Section: Discussionmentioning
confidence: 85%